Tumors induce de novo steroid biosynthesis in T cells to evade immunity - Bidesh Mahata (Nature Portfolio, 2020)
Multiple mechanisms of immune evasion exploited by cancer cells have been described. Here, the authors show that genetic inactivation or pharmacological inhibition of tumor-induced Th2-mediated de novo steroidogenesis are sufficient to restore an efficient anti-tumor immune response and restrict tumor growth.